Identification of English Needs for Taekwondo Athletes in Palu Through ESP - Zakhiyah, Rif'ah; Jamiluddin; Aminah Suriaman (Center of Language and Cultural Studies [CLCS], 2024)
The objectives of this research are to identify the perceptions of coaches/stakeholders and athletes about ESP for athlete career development, and to analyze the English needs for taekwondo athletes. This research uses a descriptive qualitative method. The respondents from this research amounted to 25 people consisting of 13 coaches/stakeholders and 12 athletes. The first result of this research is coaches/stakeholders and athletes stating that English has an important role in the career development of Taekwondo athletes. The second, analysis of the athletes' ESP needs including, 1) In the weaknesses section, the majority of coaches/stakeholders stated that taekwondo athletes could not speak English but this was denied by the athletes where the majority of them stated that they were interested and could speak a little English but because they do not realize its importance for the development of their careers as athletes and there is no environmental support that facilitates them to speak English. 2) In the Needs section, the aspects of ESP need in Taekwondo athletes that are the main concern for their development are speaking and listening skills. 3) The majority of coaches/stakeholders and athletes agree that after learning English, they want the athletes to be able to communicate in English well.